2011
DOI: 10.3141/2262-04
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Evaluations of Design Consistency for Two-Lane Highways

Abstract: Operating speed prediction models along horizontal curves of two-lane rural highways have been the topic of a significant body of literature. Operating speed models for two-lane rural highway tangents and for horizontal curves on low-speed urban streets also exist but are less developed. These models, estimated primarily by means of ordinary least squares regression, generally use aggregate-level data to estimate the effect of geometric design variables on the mean or 85th percentile operating speed but do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Previous researches (Krammes et al 1995;Hassan et al 2001;Ng, Sayed 2004;Cafiso et al 2004;Park, Saccomanno 2006;Mattar-Habib et al 2008;Cafiso, Cava 2009;Himes et al 2011) have shown that one of the main reasons for accident occurrence is the geometric design inconsistency defined as the degree to which highway systems are designed to avoid critical driving manoeuvres and ensure safe traffic operation. A consistent road design ensures harmonized driving speed, in accordance with drivers' expectations and without sur- prising events.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches (Krammes et al 1995;Hassan et al 2001;Ng, Sayed 2004;Cafiso et al 2004;Park, Saccomanno 2006;Mattar-Habib et al 2008;Cafiso, Cava 2009;Himes et al 2011) have shown that one of the main reasons for accident occurrence is the geometric design inconsistency defined as the degree to which highway systems are designed to avoid critical driving manoeuvres and ensure safe traffic operation. A consistent road design ensures harmonized driving speed, in accordance with drivers' expectations and without sur- prising events.…”
Section: Introductionmentioning
confidence: 99%
“…The operating speed dispersion is lower in this case (but higher than for horizontal curves). Himes et al (2011) found that the geometric design features on two-lane roads were not correlated with the posted speed limit. Hence, the speed limit should not be ignored as a predictor of operating speed.…”
mentioning
confidence: 95%
“…Instead, using density and V/C ratio offered a richer description. Zhou and Sisiopiku (1997) noticed that hourly crash rates presented a 'U' shape, decreasing while the V/C ratio increased.Himes, Donnell and Porter (2011) examined the influence of the hourly traffic volume on the mean speed and its dispersion. They examined 79 sites of 8 roads in Pennsylvania and Virginia, finding that the hourly traffic volume was strongly correlated to the speed dispersion.…”
mentioning
confidence: 99%
See 2 more Smart Citations